Value Relevance of Accounting Information: Evidence from Banking Industry in ASEAN - Tri Nurul Khomidah; Doddy Setiawan (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2022)
Previous research on the value relevance of accounting information and stock prices had different results. The differences in the results of this study indicate that further studies on the value relevance of accounting information and stock prices are still needed. This study investigates the relationship between the capital markets and accounting information in the banking sector of ASEAN countries, namely Indonesia, Malaysia, Singapore, Thailand and the Philippines. Specifically, this study looks at the relationship between earnings per share (EPS) and book value per share (BVPS) on the balance sheet value. Using a sample of listed banks from 2017 to 2019, this study documents accounting information in the context of emerging markets by using stock prices as the dependent variable three months after the end of the year is taken into consideration. The sample determination method for this study used a dedicated sampling method to obtain 82 samples that met the criteria. This study uses a panel data regression technique. The results of this study show that earnings and book value have a statistically positive impact on stock prices. This study also shows that revenue is more related to value than other variables